Peningkatan Kualitas Hidup Masyarakat Dikelurahan Kerta Sari Melalui Program Pembangunan Infrastruktur dan Ekonomi Berkelanjutan - Sumar Abdulah Azis (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The purpose of this study was to identify and analyze the impact of sustainable infrastructure and economic development programs on improving the quality of life of people in the Kertasari Village. Researchers used analytical techniques using quantitative methods. The research location is the Kertasari Village and this research is expected to provide recommendations for policies and development programs that are more effective and sustainable in the future. Kertasari Village is an urban village with a high population density. Despite having good human resource potential, the community's quality of life is still low. The problems faced include high unemployment rates, low living standards, limited access to basic infrastructure, and a lack of economic opportunities. Sustainable infrastructure and economic development is expected to overcome this problem. Sustainable infrastructure development programs improve access to and quality of basic services such as clean water, sanitation and proper roads. Sustainable economic development programs increase people's employment and income opportunities, as well as improve living standards. This program also has a positive impact on the environment through efficient use of energy and good waste management. This study used a quantitative method with respondents from the residents of the Kertasari Village and students. The results of previous research show that sustainable infrastructure and economic development contribute to improving people's quality of life, access to health services, education, and public facilities.